To Study AC electrical conductivity of TiO2 doped polyaniline. - et. al, N R Thakare (International Journal of Advanced Science and Technology, 2020)
In the present research work we make a pallet of PANI+TiO2 and then we determined the AC electrical conductivity of polyaniline and polyaniline doped TiO2. Effect of Temperature on A.C. conductivity at varying frequency is also studied.